Facilitating student learning about ergonomics and healthy computing skills via participatory ergonomics. - Korkmaz SV; Sommerich CM (Work, 2009)
In general, K-12 students have little opportunity to control feedback from the various factors in their educational environments. However, leading theories of human-system interaction suggest participants in a system will perform better if they have some degree of control over their interaction with the design of the system's features. In an effort to provide an added degree of control to students in one high school while also attempting to address concerns about computer use-related musculoskeletal discomfort in students, an experiment was conducted with the goal of identifying effective means through which students could learn about healthy computing. One group of students (n=8) participated in a knowledge discovery process facilitated by an ergonomist, a second group of students (n=6) participated in a training session conducted by the first group of students, and a third group served as controls (n=7). Results of a comparison of scores for pre- and post-intervention surveys that tested students' abilities to recognize problematic computer use conditions and make appropriate recommendations for change showed an increase for the first and second groups, and no increase in the control group. Another positive sign from the first group was their sustained participation, on their own time, in the learning process over the course of several weeks. Pros and cons of the learning methods are discussed.